Assessment of the effects of air pollution using road-side roasted meats (Suya) as indicators - Adebiyi, F.; Sonibare, J.; Adedosu, T.; Daramola, A.; Omode, P.; Obanijesu, Emmanuel (Taylor & Francis, 2008)
The Suya meat samples sold in the open market, roadsides and motor parks were collected from four towns in Southwestern Nigeria. The meat was investigated as a potential bioindicator of metal exposure to humans in an urban environment. These were pulverized, digested then analyzed using Atomic Absorption Spectroscopy (AAS) technique to determine the concentrations of five elements (Fe, Zn, Pb, Mn, and Cu). Iron has the highest concentrations in the range of 102 and 406 mg/kg while Mn has the least values: 4.80-15.4 mg/kg. The results show that even though meat is a rich source of essential and beneficial minerals required for healthy growth, excesses of these metals may be ingested from Suya; sources which include wood smoke, street dusts, and vehicular emissions and debris from automobile break parts are the identified origins of some of these excesses. Analysis of certified standard reference material IAEA-V-10 Hay (powder) was carried out to assure accuracy and precision of the technique. Copyright © Taylor & Francis Group, LLC.